Inovasi dan Pengembangan Sistem Evaluasi PAI di Pesantren ‘Ashriyah (Modern) Darussalam Gontor - Muhammad Rofiq; Mukh Nursikin (Journal on Education, 2023)
This study aims to examine the concept of evaluation in the verses of the Qur'an and Hadith, the philosophical concept of evaluating PAI learning, the form of innovation and development of an evaluation system for learning PAI, as well as the analysis of innovation and the development of an evaluation system for PAI learning. This research uses a literature review approach, where the researcher in this case collects sources from previous studies, books, magazines related to the problem and research objectives. As for the results of his research that the concept of evaluation in the verses of the Qur'an is Al-Hisab or al-Muhasabah, Al-Bala', Al-Hukm, Al-Qadha and Al-Nazhr. The philosophical concept of evaluating PAI learning in the philosophy of Islamic education is a picture in the mind through in-depth investigation, to the root of the problem and is thoroughly related to evaluation in PAI learning. The form of innovation and development of the PAI learning evaluation system is to adhere to the principles of comprehensiveness, the principles of continuity, the principles of objectivity, the principles of integration, and the principles of order. In the implementation of innovation and development of the PAI evaluation system at the Darussalam Gontor Islamic Boarding School, that is in accordance with the philosophical view of pragmatism, where in the implementation of education it is not only providing theoretical understanding, but it is also in accordance with the perspective of perennial philosophy, where in the implementation of education has a goal to improve the quality of students/students universally and not be affected by space and time. On the other hand, it is also in line with the philosophical view of progressivism, where students are given the freedom to be able to develop or explore their abilities.